Immunotherapy for Chronic Wounds in Aging Populations: A Scoping Review of Mechanisms, Therapeutic Agents, and Clinical Gaps - Rattanamanee, Kwanchai; Kulla, Patsanan; Thakolpattanakul, Thanaporn; Thakolpattanakul, Thanakrit; Pinyoying, Khemjira; Poowaruttanawiwit, Prayuth (Trends in Immunotherapy, 2025)
Chronic wounds in older adults are a growing concern due to impaired immunity, delayed epithelialization, and prolonged inflammation. These wounds lead to significant morbidity, increased healthcare costs, and reduced quality of life. Immunotherapies and adjunctive interventions show promise but remain insufficiently validated in geriatric populations. This study aimed to synthesize and map current evidence on immune-based strategies and supportive approaches for chronic wound management in the elderly, focusing on mechanisms, outcomes, and delivery challenges. A scoping review was conducted following the Arksey and O’Malley framework and PRISMA-ScR guidelines. Searches in PubMed, Scopus, and Web of Science, complemented by manual screening, identified eligible studies using the PCC (Population–Concept–Context) framework. Data extracted included therapeutic class, mechanism, wound type, and outcomes. Of 1,142 records, 89 met inclusion. Key immunotherapies included NLRP3 inflammasome inhibitors, regulatory T-cell modulators, and mTOR-targeted agents, which improved re-epithelialization and reduced cytokines in preclinical models. However, evidence in elderly human cohorts was scarce. Adjunctive strategies—such as protein supplementation, senescence-targeted agents, and engineered biomaterials—enhanced immunotherapy effects. Major barriers were the lack of wound-specific formulations, limited geriatric trial representation, and underdeveloped topical delivery systems. While immunotherapy shows mechanistic potential to correct immune dysregulation in chronic wounds, most data remain preclinical. Multi-modal strategies integrating immunotherapy, nutrition, and bioengineered scaffolds, tailored to aging physiology, are needed to improve outcomes and require rigorous clinical validation.